Analyzing the impact of phthalate and DINCH exposure on fetal growth in a cohort with repeated urine collection - Ouidir, Marion; Jedynak, Paulina; Rolland, Matthieu; Lyon-Caen, Sarah; Thomsen, Cathrine; Sakhi, Amrit K.; Sabaredzovic, Azemira; Bayat, Sam; Slama, Rémy; Philippat, Claire (Environment international, 2024)
•MiBP and MnBP were positively associated with most second trimester growth parameters.•At second trimester, MiBP was associated with head and abdominal circumferences.•MnBP was associated with all fetal measurements at either second or third trimester.•MnBP associations with fetal growth parameters were stronger among males.•Metabolites mixture was positively associated with fetal weight at second trimester. Most previous studies investigating the associations between prenatal exposure to phthalates and fetal growth relied on measurements of phthalate metabolites at a single time point. They also focused on weight at birth without assessing growth over pregnancy, preventing the identification of potential periods of fetal vulnerability. We examined the associations between pregnancy urinary phthalate metabolites and fetal growth outcomes measured twice during pregnancy and at birth. For 484 pregnant women, we assessed 13 phthalate and two 1,2-cyclohexane dicarboxylic acid, diisononyl ester (DINCH) metabolite concentrations from two within-subject weekly pools of up to 21 urine samples (median of 18 and 34 gestational weeks, respectively). Fetal biparietal diameter, femur length, head and abdominal circumferences were measured during two routine pregnancy follow-up ultrasonographies (median 22 and 32 gestational weeks, respectively) and estimated fetal weight (EFW) was calculated. Newborn weight, length, and head circumference were measured at birth. Associations between phthalate/DINCH metabolite and growth parameters were investigated using adjusted linear regression and Bayesian kernel machine regression models. Detection rates were above 99 % for all phthalate/DINCH metabolites. While no association was observed with birth measurements, mono-iso-butyl phthalate (MiBP) and mono-n-butyl phthalate (MnBP) were positively associated with most fetal growth parameters measured at the second trimester. Specifically, MiBP was positively associated with biparietal diameter, head and abdominal circumferences, while MnBP was positively associated with EFW, head and abdominal circumferences, with stronger associations among males. Pregnancy MnBP was positively associated with biparietal diameter and femur length at third trimester. Mixture of phthalate/DINCH metabolites was positively associated with EFW at second trimester. In this pregnancy cohort using repeated urine samples to assess exposure, MiBP and MnBP were associated with increased fetal growth parameters. Further investigation on the effects of phthalates on child health would be relevant for expanding current knowledge on their long-term effects.